KL-6 as an Immunological Biomarker Predicts the Severity, Progression, Acute Exacerbation, and Poor Outcomes of Interstitial Lung Disease: A Systematic Review and Meta-Analysis - Zhang, Tao; Shen, Ping; Duan, Chunyan; Gao, Lingyun (Frontiers in Immunology, 2021)
Object: Interstitial lung disease (ILD) is a specific form of chronic fibrosing interstitial pneumonia with various etiology. The severity and progression of ILD usually predict the poor outcomes of ILD. Otherwise, Krebs von den Lungen-6 (KL-6) is a potential immunological biomarker reflecting the severity and progression of ILD. This meta-analysis is to clarify the predictive value of elevated KL-6 levels in ILD. Method: EBSCO, PubMed, and Cochrane were systematically searched for articles exploring the prognosis of ILD published between January 1980 and April 2021. The Weighted Mean Difference (WMD) and 95% Confidence Interval (CI) were computed as the effect sizes for comparisons between groups. For the relationship between adverse outcome and elevated KL-6 concentration, Hazard Ratio (HR) and its 95%CI were used to estimate the risk factor of ILD. Result: Our result showed that ILD patients in severe and progressive groups had higher KL-6 levels, and the KL-6 level of patients in severe ILD was 703.41(U/ml) than in mild ILD. The KL-6 level in progressive ILD was 325.98 (U/ml) higher than that in non-progressive ILD. Secondly, The KL-6 level of patients in acute exacerbation (AE) of ILD was 545.44 (U/ml) higher than stable ILD. Lastly, the higher KL-6 level in ILD patients predicted poor outcomes. The KL-6 level in death of ILD was 383.53 (U/ml) higher than in survivors of ILD. The pooled HR (95%CI) about elevated KL-6 level predicting the mortality of ILD was 2.05 (1.50-2.78), as well as the HR (95%CI) for progression of ILD was 1.98(1.07-3.67). Conclusion: Elevated KL-6 level indicated more severe, more progressive, and predicted the higher mortality and poor outcomes of ILD.